(untitled) (The Research of Medical Science Review, 2025)
Objective: To examine the effect of academic self-efficacy on academic performance and time management skills, and to evaluate the mediating role of time management in the relationship between academic self-efficacy and academic performance. Methods: A cross-sectional quantitative design was employed, involving 374 medical students selected through convenience sampling. Data were collected using validated instruments for academic self-efficacy, time management behavior (Time Management Behavior Scale), and academic performance (self-reported CGPA). Data analysis included independent samples t-tests and Structural Equation Modeling (SEM) to test direct and indirect relationships. Results: Students with high academic self-efficacy scored significantly higher in both academic performance (M = 72.35, SD = 7.63) and time management skills (M = 70.45, SD = 8.12) than those with low self-efficacy (academic performance: M = 65.78, SD = 8.24; time management: M = 61.20, SD = 9.05), with large effect sizes (Cohen’s d = 0.84 and 1.02, respectively). SEM confirmed that time management partially mediated the relationship between self-efficacy and academic performance, with a significant indirect effect (β = 0.17, 95% CI [0.10, 0.25]). Conclusion: The findings support that academic self-efficacy enhances academic performance both directly and indirectly through effective time management. This mediation model, validated in a Pakistani academic context, underscores the importance of fostering both internal belief systems and behavioral skills to promote academic success.